2012
DOI: 10.1074/jbc.m111.301440
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa Exotoxin Y Is a Promiscuous Cyclase That Increases Endothelial Tau Phosphorylation and Permeability

Abstract: Background: ExoY induces inter-endothelial gaps, although the mechanisms by which this occurs are poorly understood. Results: ExoY synthesized cAMP and cGMP, which caused endothelial Tau hyperphosphorylation, accumulation of insoluble Tau, inter-endothelial cell gaps, and increased permeability. Conclusion: ExoY is a promiscuous cyclase and an edema factor. Significance: Acute Pseudomonas infections cause a pathophysiological sequela in endothelium previously recognized only in chronic neurodegenerative diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 84 publications
(84 citation statements)
references
References 80 publications
5
79
0
Order By: Relevance
“…This activator will likely be different from that for PaExoY, as the same extract that stimulated PaExoY did not stimulate VvExoY and indeed seemed to inhibit it. Another distinct difference between the two proteins is that PaExoY has been shown to also be efficient in the conversion of GTP to cGMP (53). We found that under the reaction conditions employed here, VvExoY did not function as a guanylate cyclase either during coculture with CHO cells or in vitro (data not shown).…”
Section: Discussionmentioning
confidence: 58%
“…This activator will likely be different from that for PaExoY, as the same extract that stimulated PaExoY did not stimulate VvExoY and indeed seemed to inhibit it. Another distinct difference between the two proteins is that PaExoY has been shown to also be efficient in the conversion of GTP to cGMP (53). We found that under the reaction conditions employed here, VvExoY did not function as a guanylate cyclase either during coculture with CHO cells or in vitro (data not shown).…”
Section: Discussionmentioning
confidence: 58%
“…Given the shared enzymatic properties between ExoY, CyaA, and edema factor, it was reasonable to consider that ExoY generates multiple cyclic nucleotide monophosphates. Coupling this possibility with the fact that cAMP and cGMP both influence endothelial barrier integrity, Ochoa et al (2012) hypothesized that ExoY possessed both adenylyl and guanylyl cyclase activity when introduced into pulmonary microvascular endothelial cells (PMVECs). When PMVECs were infected, ExoY intoxication generated a significantly higher (~10-fold) cGMP than cAMP signal, suggesting ExoY is principally a guanylyl cyclase (Ochoa et al 2012).…”
Section: Discovery That Exoy Is a Guanylyl Cyclasementioning
confidence: 99%
“…We have seen that ExoY functions not only as an adenylyl cyclase, but rather, as a promiscuous purine and pyrimidine nucleotidyl cyclase in vascular endothelium, generating cGMP, cAMP, cUMP and, to a lesser extent, cCMP (Morrow et al 2015). The elevation of these cyclic nucleotide monophosphates causes endothelial tau hyperphosphorylation, which leads to microtubule breakdown and endothelial hyperpermeability (Balczon et al 2013; Morrow et al 2016; Ochoa et al 2012; Prasain et al 2009; Sayner et al 2011). Hyperphosphorylation appears to trigger tau oligomerization and release, contributing to a transmissible proteinopathy that perpetuates cytotoxicity during infection (Morrow et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The method consisted of a 40-min gradient at a flow rate of 300 nl/min using a gradient from solvent A (5% acetonitrile and 0.1% formic acid in water) and solvent B (80% acetonitrile and 0.08% formic acid in water). The system includes a 300-m-by-5-mm PepMap C 18 precolumn and a 75-m-by-250-mm C 18 PepMap. MS and MS/MS data were acquired using Xcalibur (Thermo Fischer Scientific) and processed automatically using Mascot Daemon software (Matrix Science).…”
Section: Methodsmentioning
confidence: 99%
“…The main consequence of ExoS/ExoT action at the cell level is the dismantlement of the actin cytoskeleton and the focal contacts, leading to cell retraction (16). ExoY is a potent adenylate cyclase, which has no effect on cell retraction when injected alone and even induces a slight but significant spreading when cells are infected at a low multiplicity of infection (MOI) with a mutant strain secreting ExoY as the sole type 3 toxin (16,17), while ExoY induces the disruption of the microtubules at a high MOI and longer infection times (18).…”
mentioning
confidence: 99%